Transformation of Education in Maredan Barat Village: Digitalization of Village Libraries and Monographs as Pillars of Development - Eddy Noviana; Daeng Ayub; Otang Kurniaman; Muhammad Jais; Masyitha Ramadhani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Community service in Desa Maredan Barat, Tualang District, Siak Regency, aims to improve access to information and the quality of education with two main activities: digitizing village libraries and compiling village monographs. The existing village libraries will be updated with a digital library system to make it easier for the community, especially students, to access educational materials online. In addition, village monographs are compiled to comprehensively describe the village's social, economic, and academic potential. This program is implemented through the stages of identifying needs, developing training materials, implementing training, and monitoring and evaluation. The main targets are village officials and library managers. It is hoped that with the digitization of libraries and village monographs, village education and resources management can be more effective and provide an accurate basis for village development planning. Thus, Maredan Barat Village is expected to become a fostered village of FKIP Universitas Riau, which is developing in education and village resource management.